Establishing Chinese Fetal Growth Standards: Why and How - Xiaojing Zeng; Jing Zhu; Jun Zhang; Dandan Shi (Maternal-Fetal Medicine)
Abstract. Choosing a fetal growth standard or reference is crucial when defining normal and abnormal fetal growth. We reviewed the recently published standards and compared them with a customized fetal growth chart based on a nationwide population in China. There were substantial discrepancies in the fetal growth pattern, suggesting that these standards may not be applicable to Chinese fetuses. Developing a Chinese-specific standard may better meet our clinical requirements. We also discuss the steps to establish a Chinese fetal growth standard and the potential challenges, including regional disparities and accuracy of sonographic estimated fetal weight. Standardized ultrasound measurement protocol and the introduction of new ultrasonography technology may be helpful in developing a more precise standard than existing ones for the Chinese population.